2022
DOI: 10.1038/s43856-022-00204-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between structural heart disease and cardiac SARS-CoV-2 manifestations

Abstract: Background: The prognosis of COVID-19 patients with cardiac involvement is unfavorable and it remains unknown which patients are at risk. The virus enters cells via its receptor angiotensin-converting enzyme 2 (ACE2). Myocardial ACE2 expression is increased in structural heart disease (SHD). We, therefore, aimed to analyze correlations between structural heart disease and cardiac SARS-CoV-2 manifestation. Methods: The clinical course of COVID-19 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Similar results were even obtained in relation to the number of casualties [118]. Inflammation, elicited by SARS-CoV-2, exacerbated heart and blood vessel damage, as evidenced by the tropism of the virus for these cells [119,120]. Also, fibrosis-altered lung function and chronic obstructive pulmonary disease were reported as long-term COVID-19-induced sequelae in patients with tuberculosis [94,121,122].…”
Section: The Comorbidities Underlying Covid-19 Severity In Africasupporting
confidence: 71%
“…Similar results were even obtained in relation to the number of casualties [118]. Inflammation, elicited by SARS-CoV-2, exacerbated heart and blood vessel damage, as evidenced by the tropism of the virus for these cells [119,120]. Also, fibrosis-altered lung function and chronic obstructive pulmonary disease were reported as long-term COVID-19-induced sequelae in patients with tuberculosis [94,121,122].…”
Section: The Comorbidities Underlying Covid-19 Severity In Africasupporting
confidence: 71%
“…A previous study has shown that ACE2 and angiotensin (1-7) levels are reduced in autopsy heart samples from patients who tested positive ( 70 ). Despite the reduced ACE2 levels, the SARS-CoV-2 virus has a 10- to 20-fold higher affinity for binding to ACE2 receptors than SARS-CoV due to an amino acid difference in the S protein RBD.…”
Section: Molecular Mechanism Of Sars-cov-2-associated Myocarditismentioning
confidence: 99%
“…ACE2 expression was initially thought to account for mild and severe symptoms seen in most children and elderly during the early years of the COVID-19 pandemic. However, numerous reports have contradicted initial observations suggesting an inverse relationship between ACE2 expression and disease severity [ 77 ]. These contradictions were addressed in a study by Bastolla et al [ 78 ], which showed that ACE2 mRNA and protein expression is not monotonically related to age.…”
Section: Bats Pangolins Parasites and Diarylamidines: Making The Conn...mentioning
confidence: 99%